(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Prodrug technique is used to remedy some troubles and enhance the interest of medication. Diclofenac is classified as non-steroidal and anti-inflammatory drug (NSAIDS) which used as anti-inflammatory and analgesic however it has many side effects causing gastro-intestinal ulcer, gastro-esophageal reflex disease (GERD). Prodrug of diclofenac is synthesized by using coupling of amine with diclofenac and ester derivatives of amino acids production in the presence of HCl in dichloromethane. These newly synthesized prodrugs lower a number of the gastrointestinal adverse effects through covering the free carboxylic acid group to improve the bioavailability through reduction the hydrolysis by the effect of GIT enzymes. The prodrug is estimated for solubility and analyzed by using FTIR spectroscopy and nuclear magnetic resonance.